Case report: Joint diagnosis and treatment of intrathoracic gastric duplication with a gastric communication in a child by laparoscopy and gastroscopy - Zhao, Huashan; Zhai, Yunpeng; Guo, Rui; Xu, Hongxiu; Lv, Longfei; Zhang, Shisong (Frontiers in Pediatrics, 2023)
Gastric duplication associated with the stomach, located in the thorax, has rarely been reported previously. A 5-year-old child with gastric duplication located in the left thorax was diagnosed and treated successfully using laparoscopy combined with gastroscopy. Preoperative CT, upper gastrointestinal contrast study, ultrasound, and other imaging methods were insufficient for accurate diagnosis in this case. Laparoscopy combined with gastroscopy is more suitable for the diagnosis and treatment of gastric duplication.